1998
DOI: 10.1074/jbc.273.45.29915
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Membrane-bound Glutathione S-Transferase Functions in the Stationary Phase of the Yeast Saccharomyces cerevisiae

Abstract: The glutathione S-transferases (GSTs) represent a significant group of detoxification enzymes that play an important role in drug resistance in all eukaryotic species. In this paper we report an identification and characterization of the two Saccharomyces cerevisiae genes, GTT1 and GTT2 (glutathione transferase 1 and 2), coding for functional GST enzymes. Despite only limited similarity with GSTs from other organisms (ϳ50%), recombinant Gtt1p and Gtt2p exhibit GST activity with 1-chloro-2,4-dinitrobenzene as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
140
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(146 citation statements)
references
References 56 publications
4
140
0
2
Order By: Relevance
“…1), as suspected from the sequence similarity between these proteins (9,(32)(33)(34). However, it should be noted that no GST activity has been observed in Ure2p (9,32). The Ure2p(97-354) monomer has two domains and dimensions of approximately 57 Å ϫ 55 Å ϫ 36 Å.…”
Section: Resultsmentioning
confidence: 97%
“…1), as suspected from the sequence similarity between these proteins (9,(32)(33)(34). However, it should be noted that no GST activity has been observed in Ure2p (9,32). The Ure2p(97-354) monomer has two domains and dimensions of approximately 57 Å ϫ 55 Å ϫ 36 Å.…”
Section: Resultsmentioning
confidence: 97%
“…In our present study, a novel Gst Pm -4 of P. mirabilis, was identified and characterized to be involved in heavy metal resistance. Although Gst Pm -4 possesses no cysteine, it is able to conjugate the model substrates CDNB and GSH, which means it belongs to the GST superfamily [30,31]. Considering the fact that it is generally accepted that proteins with >40% sequence identity belong to the same class, Gst Pm -4 resembling a new branch GST (IsoJ) from Rhodococcus AD45 was confirmed that it belonged to a new class of GST [2].…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, GSTs use a conserved tyrosine, serine or cysteine residue to interact with the thiol group of GSH, thus increasing the reactivity of GSH, typically via a sequential mechanism [51][52][53]. In S. cerevisiae, the two GSTs that have been identified show activity towards CDNB, but do not possess peroxidase activity [54]. On the other hand, the two glutaredoxins are active towards both CDNB and hydroperoxides [55] and the three phospholipid hydroperoxide glutathione peroxidases show activity towards both lipid and non-lipid hydroperoxides [56].…”
Section: Ure2 As a Glutathione Transferasementioning
confidence: 99%
“…3). However, Ure2 does not show a detectable level of GST activity with typical substrates, such as CDNB [27,29,54,60]. Recent studies have found that deletion of the URE2 gene increases the sensitivity of S. cerevisiae cells to heavy metals and cellular oxidants, such as hydrogen peroxide [60][61][62]; and a Ure2 homologue from Aspergillus nidulans, while lacking the nitrogen metabolite repression activity of Ure2, also contributes to heavy metal and xenobiotic resistance [63].…”
Section: Ure2 As a Glutathione Transferasementioning
confidence: 99%